The Role of Traditional Chinese Medicine Natural Products in β-Amyloid Deposition and Tau Protein Hyperphosphorylation in Alzheimer’s Disease - Yan H; Feng L; Li M (Dove Medical Press, 2023)
Huiying Yan,1 Lina Feng,2 Mingquan Li1 1Department of Neurology, the Third Affiliated Clinical Hospital of the Changchun University of Chinese Medicine, Changchun, Jilin Province, People's Republic of China; 2Shandong Key Laboratory of TCM Multi-Targets Intervention and Disease Control, the Second Affiliated Hospital of Shandong First Medical University, Taian, Shandong Province, People's Republic of ChinaCorrespondence: Lina Feng, The Second Affiliated Hospital of Shandong First Medical University, Yingsheng Road 2, Taian, Shandong Province, 271000, People's Republic of China, Tel +86-15543120222, Email fenglina0001@163.com Mingquan Li, The Third Affiliated Clinical Hospital of the Changchun University of Chinese Medicine, Boshuo Road, Changchun, Jilin, 130117, People's Republic of China, Tel +86-15948000577, Email Limingquan0001@126.comAbstract: Alzheimer's disease is a prevalent form of dementia among elderly individuals and is characterized by irreversible neurodegeneration. Despite extensive research, the exact causes of this complex disease remain unclear. Currently available drugs for Alzheimer's disease treatment are limited in their effectiveness, often targeting a single aspect of the disease and causing significant adverse effects. Moreover, these medications are expensive, placing a heavy burden on patients' families and society as a whole. Natural compounds and extracts offer several advantages, including the ability to target multiple pathways and exhibit high efficiency with minimal toxicity. These attributes make them promising candidates for the prevention and treatment of Alzheimer's disease. In this paper, we provide a summary of the common natural products used in Chinese medicine for different pathogeneses of AD. Our aim is to offer new insights and ideas for the further development of natural products in Chinese medicine and the treatment of AD.Keywords: Alzheimer's disease, β-amyloid deposition, tau-protein hyperphosphorylation, natural products, Chinese herbal medicine, review